2003
DOI: 10.1002/ppul.10233
|View full text |Cite
|
Sign up to set email alerts
|

Negative expiratory pressure: A new tool for evaluating lung function in children?

Abstract: The negative expiratory pressure technique (NEP) has been applied in adults with chronic obstructive pulmonary disease (COPD), demonstrating flow limitation in many of these patients. Because this technique does not require patient cooperation, it is of potential interest for application in the pediatric population. This study was performed to test the feasibility of NEP in children, and to further investigate it in children with asthma and cystic fibrosis (CF). We performed NEP (0.3-0.7 kPa) measurements in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…This parameter is calculated as TIF50 SLP /TEF50 SLP and can be considered analogous to the traditional “flow/volume-based” tidal breathing parameter, IE50 (the ratio of inspiratory to expiratory flow at 50% of tidal volume [TIF50/TEF50]). The effects of the COPD disease state on IE50 SLP , IE50, or related parameters have not been reported before, as such parameters have mainly been described in children with asthma or other respiratory disease 21. The CLES associated with IE50 SLP (84.6%, approximately equivalent to an effect size of 1.4 had the distribution been normal) is very large, which is an indication of the ability of the parameter in distinguishing COPD from health.…”
Section: Discussionmentioning
confidence: 94%
“…This parameter is calculated as TIF50 SLP /TEF50 SLP and can be considered analogous to the traditional “flow/volume-based” tidal breathing parameter, IE50 (the ratio of inspiratory to expiratory flow at 50% of tidal volume [TIF50/TEF50]). The effects of the COPD disease state on IE50 SLP , IE50, or related parameters have not been reported before, as such parameters have mainly been described in children with asthma or other respiratory disease 21. The CLES associated with IE50 SLP (84.6%, approximately equivalent to an effect size of 1.4 had the distribution been normal) is very large, which is an indication of the ability of the parameter in distinguishing COPD from health.…”
Section: Discussionmentioning
confidence: 94%
“…; Tauber et al. ). A reduction in TEF50, without a reduction in TIF50, would increase IE50 and explain the higher median IE50 SLP observed in our study.…”
Section: Discussionmentioning
confidence: 97%
“…The Tauber study demonstrated that reductions in airway resistance following bronchodilator administration increased expiratory flow (Tauber et al. ). TEF50, however, did not return to “normal.” In our study, mIE50 decreased after bronchodilator but remained higher than in healthy children.…”
Section: Discussionmentioning
confidence: 99%